Academic librarians and searchers: A new collaboration sets the path towards research project success - Meyer, Camille (Qualitative and Quantitative Methods in Libraries, 2017)
Digital libraries develop more and more partnerships with research teams. In France, the study case of the research project "Childhood, Violence, and Exil" testifies to the fact that librarians play a new role in research investigation.  We will focus our paper on the description of the different kind of resources of this project, which has allowed new kind of research collaboration between searchers and librarians.